2014
DOI: 10.1590/1809-4503201400060006
|View full text |Cite
|
Sign up to set email alerts
|

Social factors associated with mental disorders with risk situations in the primary health care

Abstract: The availability and access to social and support networks are lower for patients with MD-WR and need to be strengthened to promote autonomy and citizenship among its users. We conclude that there is the need of public policies to increase the availability of social networking equipment and social support projects, encouraging the participation of families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, this effect was found to be more prevalent in women than men, and amongst those with lower self-esteem than those with greater support from family and friends. Drummond et al [25] found that only gender had a signi cant effect on the risk of mental disorders in Brazil, while the World Health Organization [26] showed that economic factors, including unemployment, poverty, income inequality and debt, as well as social factors, such as education and family problems, could cause mental illness. On the other hand, Joshi [27] found that lower house prices reduced people's wealth, thus increasing the number of self-reported mental health issues in the US.…”
Section: Sourcementioning
confidence: 99%
“…Moreover, this effect was found to be more prevalent in women than men, and amongst those with lower self-esteem than those with greater support from family and friends. Drummond et al [25] found that only gender had a signi cant effect on the risk of mental disorders in Brazil, while the World Health Organization [26] showed that economic factors, including unemployment, poverty, income inequality and debt, as well as social factors, such as education and family problems, could cause mental illness. On the other hand, Joshi [27] found that lower house prices reduced people's wealth, thus increasing the number of self-reported mental health issues in the US.…”
Section: Sourcementioning
confidence: 99%